Bill of Quantity Analysis for GPON-Based FTTH Network Planning in Taman Asri 8 Residential Area Padang - Nisa Rahima Sakinah Nisa; Uzma Septima; Nasrul Nasrul (Politeknik Negeri Padang, 2026)
The increasing demand for high-speed broadband internet services requires reliable and efficient access network infrastructure. The Taman Asri 8 residential area in Padang City has the potential for broadband service development; however, MyRepublic has not yet deployed a Fiber to the Home (FTTH) network in this area. This study aims to design a Gigabit Passive Optical Network (GPON)-based FTTH network and develop a Bill of Quantity (BoQ) as an estimation of the network equipment required for deployment. The materials used in this study include the residential site plan, field survey data, and geographic information obtained from Google Earth Pro, while AutoCAD was employed to develop the network layout. The proposed network was designed using the Network Planning Process (NPP), which consists of requirement analysis, desktop survey, field survey, network design, and BoQ calculation. Based on the planning results, the designed FTTH network is capable of serving 212 homepass distributed across the residential area. The network design includes the determination of feeder and distribution routes, placement of Optical Distribution Cabinets (ODCs), Optical Distribution Points (ODPs), and other supporting optical components. Furthermore, the BoQ provides a comprehensive list of the required network devices and materials, including fiber optic cables, OLT, ODC, ODP, splitters, ONTs, and supporting accessories required for network deployment. The resulting BoQ can serve as a practical reference for network implementation planning and material procurement in similar FTTH deployment projects, thereby supporting more efficient broadband infrastructure development in residential areas.